2017
DOI: 10.1038/srep40222
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of Cry2Aa-binding proteins and their receptor function in Spodoptera exigua

Abstract: The bacterium Bacillus thuringiensis produces Crystal (Cry) proteins that are toxic to a diverse range of insects. Transgenic crops that produce Bt Cry proteins are grown worldwide because of their improved resistance to insect pests. Although Bt “pyramid” cotton that produces both Cry1A and Cry2A is predicted to be more resistant to several lepidopteran pests, including Spodoptera exigua, than plants that produce Cry1Ac alone, the mechanisms responsible for the toxicity of Cry2Aa in S. exigua are not well und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Since polycalin was first reported it could strongly bind with Cry1A toxins (Hossain et al, 2004(Hossain et al, , 2005, later the result showed polycalin also could bind with Cry2Aa in Spodoptera exigua and H. armigera (Qiu et al, 2017;Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Since polycalin was first reported it could strongly bind with Cry1A toxins (Hossain et al, 2004(Hossain et al, , 2005, later the result showed polycalin also could bind with Cry2Aa in Spodoptera exigua and H. armigera (Qiu et al, 2017;Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Since polycalin was first reported it could strongly bind with Cry1A toxins (Hossain et al, 2004, 2005), later the result showed polycalin also could bind with Cry2Aa in Spodoptera exigua and H. armigera (Qiu et al, 2017; Wang et al, 2019). Overexpression or down expression of the receptors have always been used to study the function of binding proteins in the mode action of Bt toxins.…”
Section: Discussionmentioning
confidence: 99%
“… 43 However, both Cry2Aa and Cry1Ca bind to V‐ATPase A from Chilo suppresalis and V‐ATPase A down‐regulation reduces susceptibility, 42 in agreement with a relevant role for binding to V‐ATPase A in toxicity. Orthologues of P. xylostella V‐ATPase A were proposed as binding proteins for Cry1Ac in Heliothis virescens , 23 for Cry2Aa in Spodoptera exigua 44 and for Cry8Ea3 in the scarab Holotrichia parallela 45 . Binding of Cry1A or GEAb‐dV L to V‐ATPase A may result in non‐functional V‐ATPase pumps, 46 altering gut homeostasis and probably resulting in toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…often coupled with tandem liquid chromatography-mass spectrometry (LC-MS/MS) analysis. Examples include actin, vacuolar ATP synthase (V-ATPase) subunits A and B, heat shock cognate protein, polycalin, and prohibitin 25,[29][30][31][32][33][34] . Additional functional validation would provide a better understanding of the role that these interacting proteins might play as bona fide receptors in vivo resulting in toxicity.…”
Section: Western Corn Rootworm (Wcr) Diabrotica Virgifera Virgifera mentioning
confidence: 99%